Study guides

☆☆

Q: How do you simplify 6m plus m plus m plus 4y plus n plus y plus 12 plus 2n?

Write your answer...

Submit

Still have questions?

Related questions

Factor out the 4. The answer is y-3/y+3

3x + 7y

22 + y

6x plus 4y

That will depend on the plus or minus value of 4y in order to simplify the given expression

3

(4x + 12)/(8x - 4y) = [4(x) + 4(3)]/(4(2)(x) - 4y] = 4(x + 3)/4(2x - y) = (x+ 3)/(2x - y)

4y -5

what is 4plus 12

Add like terms: (4y - y) + (23 - 6) = 3y + 17

It is: 3y-6

4y+4 = 2y+12 4y-2y = 12-4 2y = 8 y = 4

People also asked